Impact of a Suicide‐Specific Intervention within Inpatient Psychiatric Care: The Collaborative Assessment and Management of Suicidality. Issue 5 (12th January 2015) - Ellis, Thomas E.; Rufino, Katrina A.; Allen, Jon G.; Fowler, James C.; Jobes, David A.
<x xml:space="preserve">Abstract</x> A growing body of literature indicates that suicidal patients differ from other psychiatric patients with respect to specific psychological vulnerabilities and that suicide‐specific interventions may offer benefits beyond conventional care. This naturalistic controlled‐comparison trial (n = 52) examined outcomes of intensive psychiatric hospital treatment (mean length of stay 58.8 days), comparing suicidal patients who received individual therapy from clinicians utilizing the Collaborative Assessment and Management of Suicidality (CAMS) to patients whose individual therapists did not utilize CAMS. Propensity score matching was used to control for potential confounds, including age, sex, treatment unit, and severity of depression and suicidality. Results showed that both groups improved significantly over the course of hospitalization; however, the group receiving CAMS showed significantly greater improvement on measures specific to suicidal ideation and suicidal cognition. Results are discussed in terms of the potential advantages of treating suicide risk with a suicide‐specific intervention to make inpatient psychiatric treatment more effective in reducing risk for future suicidal crises.